The social responsiveness scale is an efficient screening tool for autism spectrum disorder traits in adults with anorexia nervosa. (3rd April 2020) - Kerr‐Gaffney, Jess; Harrison, Amy; Tchanturia, Kate
Abstract: Objective: A significant proportion of individuals with anorexia nervosa (AN) show high levels of autism spectrum disorder (ASD) traits, a factor associated with poorer treatment outcomes. An important question for both researchers and clinicians relates to how ASD traits should be assessed in individuals with AN. This study aimed to examine scores on the Social Responsiveness Scale adult self‐report version (SRS‐2) in individuals in the acute (AN) and recovered stages (REC) of illness compared to healthy controls (HCs). We also aimed to examine associations between the SRS‐2 and an observational diagnostic measure, the Autism Diagnostic Observation Schedule ‐ second edition (ADOS‐2). Method: The SRS‐2 and ADOS‐2 were administered to 142 adults with AN, REC, and HCs. Eating disorder (ED) psychopathology and functional impairment were also assessed. Results: AN and REC scored significantly higher than HCs on the SRS‐2. SRS‐2 scores significantly predicted ADOS‐2 classification and were positively associated with ED psychopathology and functional impairment. SRS‐2 scores were not associated with BMI or illness duration. Conclusions: The SRS‐2 may be a useful tool in screening for ASD traits in individuals with AN. Although cross‐sectional, the results also suggest ASD symptoms are independent of BMI and persist in individuals recovered from AN.